Analisis Faktor PDRB Menurut Pengeluaran Yang Mempengaruhi Laju Pertumbuhan Ekonomi Provinsi Sulawesi Selatan - Khaidarsyah Khaidarsyah; Isma Muthahharah (Inferensi, 2022)
Factor analysis can be used to track the Gross Regional Domestic Product sector that affects the rate of economic growth. Based on data obtained from the Central Statistics Agency of South Sulawesi Province, there was a significant increase from 2010 to 2021, for example, household consumption expenditure in 2010 was 100 and in 2021 it rose to 167 and that applies to all components of expenditure. This type of research uses a quantitative research approach. The data used is secular data obtained from the BPS publication of South Sulawesi Province, where the object of research is Gross Regional Domestic Product by expenditure with 8 sectors for the last 12 years, namely from 2010-2021. All expenditure component variables are eligible for factor analysis because they have met the data adequacy test and the data freedom test, and only 1 factor is formed. The expenditure component in GRDP has a very strong relationship because it has a value > 0.5 which can be said that the Expenditure Component consists of Household Consumption, LNPRT Consumption, Government Expenditure, Gross Fixed Capital Formation, Changes in Inventory, Foreign Exports, Foreign Imports, Inter-regional Net Exports affect the economic growth rate of South Sulawesi Province. The most dominant variable is Gross Fixed Capital Formation because it has a greater correlation value among other variables.